Guided discovery model: An alternative to enhance students’ critical thinking skills and critical thinking dispositions - Sri Hastuti Noer (Jurnal Riset Pendidikan Matematika, 2018)
This current study aimed to determine the effectiveness of the guided discovery model in increasing students' critical thinking skills and critical thinking dispositions. Each experiment and control group consisted of 34 students of grade X of one high school class in Bandar Lampung city. The data were obtained through mathematical critical thinking skills test and critical thinking dispositions scale. The data were analyzed qualitatively and quantitatively to obtain a comprehensive description of the impact of learning on the increase in both skills. The results showed that the increase of students’ critical thinking skills and critical thinking dispositions after learning was in the effective category. Other finding showed that the use of a contextual problem in the beginning of learning could trigger students to activate their prior knowledge. In this way, students used some strategies and made an appropriate conclusion confidently. This study suggested that the guided discovery model can be an alternative to improve students' critical thinking skills and critical thinking dispositions.